(untitled) (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Retnowati D, Solihin DD, Ghulamahdi M, Lestari. 2021. Next-generation sequencing-based Actinobacteria community associated with Callyspongia sp. from Kepulauan Seribu Marine National Park, Jakarta, Indonesia. Biodiversitas 22: 3702-3708. Sponges are sessile benthic filter-feeding animals, which harbor numerous microbes. The enormous community and abundance of sponge-associated actinobacteria envisage sponges as hot spots of microbes. The metagenomic approach with Next Generation Sequencing (NGS) technology was used to investigate the actinobacteria community of Callyspongia sp. collected from Kepulauan Seribu Marine National Park, Indonesia. Fourteen actinobacteria families were found associated with the sponge. Among them, Microbacteriaceae was the most dominant family. The community of actinobacteria was higher than that of the culturable method from our previous study. The research showed that a metagenomic approach using NGS technology reveals better information regarding the actinobacteria community associated with Callyspongia sp.